Ensino de funções por meio da videoanalise: um contributo da engenharia didática - Oliveira, Meirivâni Menezes de (2019)
This research has as the focus to verify how didactic situations guided by the use of the app VidAnalysis contributed in the teaching of the functions. As a research methodology, the didactic engineering (1980) was adopted which has four phases that is important to know: The Priori Preliminary analysis and the Experimentation and Post-Validation Analysis. In the preliminary analysis, it was sought to understand the development of this concept along the history of the math, how it was worked in the didactic books produced in Brazil since the beginning of the twentieth century and also to understand how the changing in several laws that rule the public education in Brazil allowed the exploration of this concept through the teaching directed to the development of the competences and abilities and the active methodologies allied to the use of the technologies of information and communication. When this study was finished, three didactic situations were elaborated and guided by the use of the App VidAnalysis, which were presented in the Priori Analyzes. These situations had as a theoretical reference the theory of the didactic situations of Guv Brousseau (1988) which permitted the identification of the learning process of the students in the situations of action, formulation and validation. The application of these situations detailed in the phase of Experimentation happened in the months of May and June in two schools of the public state education and it counted with the participation of 15 students. In order to the validation of the research, the priori and the posteriori analyzes were confronted, where it was noticed mainly that, although the students showed difficulties in some basic concepts, the study of the functions through the didactic situations mediated by the video analysis contributed not only for the collecting of the data from a real movement, but for the students to visualize the graphs and the tables to conjecture and validate their answers and it also made this teaching methodology a viable means for the learning and for the teaching of the functions. Finally, the data collected through this research allowed the construction of an e-book, which presents four didactic situations that explore the concept of the functions mediated by the VidAnalysis application and a website with videos and app tips for the high school teacher.